Modelo para obtenção de incentivos fiscais de ICMS aplicados à cadeia produtiva da construção: uma análise da indústria de cerâmica vermelha - FARIAS JUNIOR, Claudionor Andrade (Universidade Federal do Pará, 2023)
This thesis aims to analyze and propose guidelines to the criteria inherent to the ICMS legislation applied to Industries in General, establishing a model directed to the Construction Production Chain with emphasis on the Pará Red Ceramics Industry. To this end, it adopted theoretical concepts related to the characterization of its research universe as well as the main aspects pertinent to fiscal taxation in the referred chain, distancing itself from the legal and accounting approaches. As a central reference of the study, the model recommended by the state law of Pará, which provides for special tax treatment applicable to “industries in general”, is notable. To carry out the investigation, the quantitative research method was adopted, with the application of an electronic questionnaire to the group of industries belonging to the main ceramic pole in the northern region of Brazil. From the realization of the field research, the quantitative data collected were analyzed through the use of statistical techniques of descriptive and inferential analysis (multiple linear regression, cluster analysis, and analysis of variance). The results obtained give rise to divergent positions related to the theoretical and empirical validation of the original model. As for the empirical compartment, it is suggested: (1) the revision of the way of measuring the data referring to the variables “Innovation” and “Sustainability, with emphasis on gaining variability in the related data; and (2) the review of the scores (weights) attributed to these two variables, with emphasis on their corresponding levels of benefits achieved. As a relevant result, it is also worth highlighting the mapping of the investigated sector, highlighting: (1) the assessment of the framework of the companies participating in the research, concerning the reach of the different levels of benefit; and (2) the grouping of units (firms), considering the measure of similarity of the responses obtained. Conclusively, as a theoretical and managerial contribution, we highlight the filling of an important gap in the field of study related to the tax benefits applied to the construction production chain, such as the emphasis on the importance of a scientific foundation for the formulation of legislation associated with global public policies. Particularly, the contribution directed to the legislators of the different states of the federation, supporting the reflection and discussion about the impact of the variables "Innovation" and "Sustainability" in increasing the condition of competitiveness for companies.